Preparation and performance on polycarbonate of B/F/Si-containing hybrid coatings - KAHRAMAN, MEMET VEZİR (WILEY-BLACKWELL, 2013)
A series of UV-curable B/F/Si-containing hybrid coatings was prepared by the anhydrous sol-gel technique. The chemical structure of the coatings was characterized by FTIR, RTIR, and 1HNMR techniques. The UV-curable coatings were applied to polycarbonate substrates. The physical and mechanical properties of the UV-cured coatings, such as pendulum hardness, pencil hardness, contact angle, gel content, MEK rubbing test values, tensile strength, abrasion resistance, and gloss, were examined. Thermal gravimetric analysis (TGA) was done. The relative flammability of the hybrid coatings was tested by the limiting oxygen index (LOI) method. Results of all analyses conducted on the free films and coatings are discussed. J. VINYL ADDIT. TECHNOL., 19:3946, 2013. (c) 2013 Society of Plastics Engineers
Keywords: MECHANICAL-PROPERTIES; PHENYLBORONIC ACIDS; BOROSILOXANE GELS; BISPHENOL; MONOMERS; POLYMERS; RESINS